Optimization of Fluorometric Assay for Ozone in Solution - Hiromi Nagano; Gotaro Shiota; Hidetoshi Arakawa (Journal of Analytical Methods in Chemistry)
Ozone is widely used for sterilization, deodorization, and cleaning. However, the effects of ozone on human are not well understood, because there is currently no reliable assay method for ozone. Therefore the accurate measurement of ozone is important for its safe use. Here, we report optimized conditions for use with fluorescein derivative 1 (probe 1). Under optimum conditions, probe 1 reacted with ozone quantitatively and specifically to generate a fluorescent substance with an excitation maximum at 493 nm and an emission maximum at 523 nm. We conclude that this assay will be useful for quantifying ozone in solution.